Europaphos nº 2, 1993. Recent developments in the Teaching of Ancient Greek Language and Civilitation in Europe 1991-1993, 50 pp. (Minerva, 2019)
Review: Europaphos nº 2, 1993. Recent developments in the Teaching of Ancient Greek Language and Civilitation in Europe 1991-1993, 50 pp.